2021
DOI: 10.1177/12034754211035093
|View full text |Cite
|
Sign up to set email alerts
|

Novel Education Modules Addressing the Underrepresentation of Skin of Color in Dermatology Training

Abstract: Background Representative images of pathology in patients with skin of color are lacking in most medical education resources. This particularly affects training in dermatology, which relies heavily on the use of images to teach pattern recognition. The presentation of skin pathology can vary greatly among different skin tones, and this lack of representation of dark skin phototypes challenges providers’ abilities to provide quality care to patients of color. In Botswana and other countries in sub-Saharan Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…It is also possible that the differences in unplanned readmission, which drove the difference in severe systemic complications, is a reflection of known care disparities affecting individuals with darker skin. There is growing evidence that medical professionals do not have sufficient training to effectively identify many dermatologic and other conditions in individuals with darker skin 35,36. As hematoma requiring surgical drainage is the major cause of unplanned readmission, it is plausible that this lack of training is affecting postsurgical risk as well.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the differences in unplanned readmission, which drove the difference in severe systemic complications, is a reflection of known care disparities affecting individuals with darker skin. There is growing evidence that medical professionals do not have sufficient training to effectively identify many dermatologic and other conditions in individuals with darker skin 35,36. As hematoma requiring surgical drainage is the major cause of unplanned readmission, it is plausible that this lack of training is affecting postsurgical risk as well.…”
Section: Discussionmentioning
confidence: 99%
“…Though not assessed in this study, other modules have demonstrated the durability of the learned material over time when utilizing PALMs. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Inadequate representation in patient education materials concerning ALM and skin of color education persists throughout medical education. Physicians are a trusted source of information for patients; however, the material from which they are taught does not sufficiently represent a large, diverse and growing part of the US population (Alvarado & Feng, 2021; Colby & Ortman, n.d.; Hereford et al, 2021; Kundu et al, 2010; Okoro, 2021; Slaught et al, 2022). Louie and Wilkes (2018) conducted an analysis of the imagery depicted in commonly assigned medical school textbooks including US editions of Atlas of Human Anatomy (2014), Bates' Guide to Physical Examination and History Taking (2013), Clinically Oriented Anatomy (2014), and Gray's Anatomy for Students (2015).…”
Section: Medical Education Insufficienciesmentioning
confidence: 99%
“…Inadequate representation in patient education materials concerning ALM and skin of color education persists throughout medical education. Physicians are a trusted source of information for patients; however, the material from which they are taught does not sufficiently represent a large, diverse and growing part of the US population (Alvarado & Feng, 2021;Colby & Ortman, n.d.;Hereford et al, 2021;Kundu et al, 2010;Okoro, 2021;Slaught et al, 2022). White patients, and when looking at skin tone specifically, 93% of cancer-related images were shown on "light" skin, 6.7% were shown on "medium skin"; none of the images depicted "dark" skin (Louie & Wilkes, 2018).…”
Section: Medic Al Educ Ation Insufficien Cie Smentioning
confidence: 99%